2019
DOI: 10.1136/bmjopen-2017-020900
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics: population epidemiology and concordance in Australian children aged 11–12 years and their parents

Abstract: ObjectivesNuclear magnetic resonance (NMR) metabolomics is high throughput and cost-effective, with the potential to improve the understanding of disease and risk. We examine the circulating metabolic profile by quantitative NMR metabolomics of a sample of Australian 11–12 year olds children and their parents, describe differences by age and sex, and explore the correlation of metabolites in parent–child dyads.DesignThe population-based cross-sectional Child Health CheckPoint study nested within the Longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 37 publications
(39 reference statements)
6
85
1
Order By: Relevance
“…A large familial resemblance in metabolite concentrations has been suggested, which seems to be largely genetic (Draisma et al 2013;Kettunen et al 2016;Rueedi et al 2014). In cross-sectional studies, correlations of metabolites between parents and their offspring vary strongly, ranging from weak to relatively strong (Ellul et al 2019;Halvorsen et al 2015;Ohlund et al 2011). Partly in line with these previous studies, we observed that AA and NEFA concentrations were lower in childhood as compared to cord blood samples, whereas concentrations of PL and Carn were higher in childhood.…”
Section: Interpretation Of Main Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…A large familial resemblance in metabolite concentrations has been suggested, which seems to be largely genetic (Draisma et al 2013;Kettunen et al 2016;Rueedi et al 2014). In cross-sectional studies, correlations of metabolites between parents and their offspring vary strongly, ranging from weak to relatively strong (Ellul et al 2019;Halvorsen et al 2015;Ohlund et al 2011). Partly in line with these previous studies, we observed that AA and NEFA concentrations were lower in childhood as compared to cord blood samples, whereas concentrations of PL and Carn were higher in childhood.…”
Section: Interpretation Of Main Findingssupporting
confidence: 90%
“…Differences in these factors between mothers and their children and over time might explain the weak correlations between different time points. Previous studies observed sex differences in metabolite concentrations in both children and adults (Ellul et al 2019;Teodoro-Morrison et al 2015). We did not observe metabolite concentrations to vary between the sexes.…”
Section: Interpretation Of Main Findingscontrasting
confidence: 63%
See 2 more Smart Citations
“…Major challenges exist translating metabolomic biomarkers from discovery to application in population health studies that characterize human biology focused on systemic metabolism [2][3][4][32][33][34][35]. Wide chemical diversity and the presence of isomers and isobaric compounds prevent a single bioanalytical platform from providing all-inclusive discovery of metabolites in a biological system.…”
Section: Current Challengesmentioning
confidence: 99%